HAMBATAN IMPLEMENTASI AKUNTANSI HIJAU PADA UMKM DI KEPULAUAN RIAU - Purba, Mortigor Afrizal; Suali, Suali; Simanjuntak, Jakhon Pahala (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
Green accounting is an accounting approach that incorporates environmental considerations into financial reporting and decision-making. Despite its potential benefits, the adoption of green accounting among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in the Riau Archipelago, remains limited. This study aims to identify and analyze the barriers to implementing green accounting in MSMEs. A quantitative research design was applied, with primary data collected through questionnaires distributed to MSME owners across several districts in the Riau Archipelago. Data were analyzed using linear regression with SPSS. The results indicate that limited knowledge, lack of training, low environmental awareness, and inadequate policy support are significant barriers to green accounting adoption. The study recommends increasing education and providing policy incentives to foster the implementation of green accounting in MSMEs.